Methods of recognition by the agent of the unknown environment - Yalovets, A.L. (Інститут програмних систем НАН України, 2019)
The methods used by the agent to recognize an unknown environment are outlined. They include: a method for determining the distance to the nearest visible object and the coordinates of the intersection with this object of the beam (as a simulated direction of the agent's view) directed from the agent; the method of dynamically changing the gradation of the beam angle directed by the agent into the environment; a method for constructing a set of points belonging to objects of the environment visible from the point of the current location of the agent; the method of agent's summarizing a set of points with the construction of semantic map fragments of unknown environment; methods of recognition of the corners of rooms in the environment.Problems in programming 2019; 1: 78-89